Role of Intestinal Microbiota in Transformation of Bismuth and Other Metals and Metalloids into Volatile Methyl and Hydride Derivatives in Humans and Mice - Michalke, Klaus; Schmidt, Annette; Huber, Britta; Meyer, Jörg; Sulkowski, Margareta; Hirner, Alfred V; Boertz, Jens; Mosel, Frank; Dammann, Philip; Hilken, Gero; Hedrich, Hans J; Dorsch, Martina; et al. (Applied and Environmental Microbiology, 2008)
The present study shows that feces samples of 14 human volunteers and isolated gut segments of mice (small intestine, cecum, and large intestine) are able to transform metals and metalloids into volatile derivatives ex situ during anaerobic incubation at 37°C and neutral pH. Human feces and the gut of mice exhibit highly productive mechanisms for the formation of the toxic volatile derivative trimethylbismuth [(CH₃)₃Bi] at rather low concentrations of bismuth (0.2 to 1 μmol kg⁻¹ [dry weight]). An increase of bismuth up to 2 to 14 mmol kg⁻¹ (dry weight) upon a single (human volunteers) or continuous (mouse study) administration of colloidal bismuth subcitrate resulted in an average increase of the derivatization rate from approximately 4 pmol h⁻¹ kg⁻¹ (dry weight) to 2,100 pmol h⁻¹ kg⁻¹ (dry weight) in human feces samples and from approximately 5 pmol h⁻¹ kg⁻¹ (dry weight) to 120 pmol h⁻¹ kg⁻¹ (dry weight) in mouse gut samples, respectively. The upshift of the bismuth content also led to an increase of derivatives of other elements (such as arsenic, antimony, and lead in human feces or tellurium and lead in the murine large intestine). The assumption that the gut microbiota plays a dominant role for these transformation processes, as indicated by the production of volatile derivatives of various elements in feces samples, is supported by the observation that the gut segments of germfree mice are unable to transform administered bismuth to (CH₃)₃Bi.